Endophthalmitis following Suture Removal – Clinical Outcomes and Microbiological Profile. (17th February 2019) - Panchal, Bhavik; Tyagi, Mudit; Pathengay, Avinash; Sharma, Savitri; Dave, Vivek P; Gandhi, Uppal; Balakrishnan, Divya; Pappuru, Rajeev R.; Joseph, Joveeta; Kekunnaya, Ramesha; Das, Taraprasad
ABSTRACT: Aims : To review the clinical proﬁle and report the microbiology and treatment outcomes of endophthalmitis following suture removal. Methods : In this multi-center, retrospective interventional case series, 11 eyes of 11 patients who developed endophthalmitis following suture removal from January 2006 to December 2017 were reviewed. Results : Nine of the 11 patients developed a culture-proven, acute onset endophthalmitis [5.3 ± 3.1 days (range 2–10 days)]. Mean age was 15.8 ± 21.2 years (median 7; range, 1–66 years). Presenting visual acuity was extremely low ranging from light perception (PL) to counting fingers close to face (CFCF) at the time of diagnosis of endophthalmitis. Out of the 11 patients, 8 belonged to the pediatric age group; four out of those eight had loose sutures secondary to cataract surgery, two patients had loose sutures secondary to penetrating keratoplasty and 1 case each had loose sutures secondary to corneal tear repair and secondary IOL implantation, respectively. Streptococcus pneumoniae was the most common organism and was identified in seven cases and was susceptible to vancomycin in all these cases. Other bacterial isolates were Haemophilus influenzae and Achromobacter denitrificans . Three out of the 11 eyes had visual outcome of 20/200 or better. Six eyes were phthisical and one eye was eviscerated. Mean follow-up was 26.3 ± 31.2 weeks (range 2–92 weeks). Visual outcomes ranged from 20/40 to no light perception at the last follow-up. Conclusions : Endophthalmitis following suture removal though rare, is observed most commonly in the pediatric population and has an acute and a fulminant course. Streptococcus pneumoniae was the most commonly isolated microorganism. Visual acuity outcomes were poor despite prompt recognition of endophthalmitis and appropriate antibiotic therapy.